Hyperpronation versus Supination–Flexion in Radial Head Subluxation Reduction: A Randomized Controlled Trial - Porozan, Samaneh; Forouzan, Arash; Hassanzadeh, Rayeheh (Journal of Pediatric Intensive Care, 2020)
Radial head subluxation (RHS) is the most common upper extremity injury in children. Supination–flexion (SF) and hyperpronation (HP) are two methods for reducing this subluxation. This study purposed to compare the success rates of two methods of reduction and also to determine which technique would be less painful. In total, 154 patients with RHS were enrolled in this study and randomized into two groups. Patients were to undergo reduction by one of the two methods; if the primary attempt was unsuccessful, a second attempt was performed using the alternate technique. In the case of failure of the second attempt, the first reduction technique was repeated. The success rates and pain levels before and after successful reduction were recorded. On the first attempt, 72 of 77 patients who underwent HP had a successful reduction. Four patients in the HP group had a successful reduction on the second attempt. In the SF group, 76 of 77 patients had a successful reduction on the first attempt. The success rate on first attempts was higher in the SF group than in the HP group (p = 0.043). Pain levels before and after reduction were not statistically different between the groups (p > 0.05). The SF technique had a higher success rate at first attempt to reduce RHS, but pain levels were similar in both methods.
Keywords: radial head subluxation; supination–flexion; hyperpronation; emergency medicine